Produção animal em sistema de integração lavoura-pecuária em função de intensidade de pastejo e antecipação de adubação nitrogenada - Rissi, Bruno Felipe (2015)
The crop-livestock integration allows crops diversification in system and increased productivity per unit area, which gives higher income to producer and the efficient use of inputs. The black oat intercropped with ryegrass succession - has been widely used in this system. However, most producers don´t apply fertilizer on shieling considering that fertilization´s residual carried out effect isn´t efficient successor to culture. The study´s objective is to find the residual effect of the nitrogen fertilization´s application carried out in preceding crop grassland and the effect of different heights grazing on performance, animals' feeding behavior and chemical forage´s composition during winter / spring of the year 2014. The job was conducted at Fazenda Pacheco, located in the city of Abelardo Luz-SC coordinates, latitude: 26.5672, longitude: -52.3339. The experimental design was randomized blocks in a 2x2 factorial plan with three replications. The first factor was nitrogen fertilization Time: N-grazing 200 kg ha-1 and N-grains. The second factor was the grazing height, characterized by high grazing height (30 cm) and Low grazing height (15 cm). Nitrogen fertilization´s application in maize crop in crop-livestock integration system in southern Brazil has no residual effect on the pastures' performance leading to lower animal production. Nitrogen fertilization when applied on grassland has an effect on the increase in dry matter production of the pasture providing greater stocking rate but doesn't change the pasture´s qualitative content. The pasture management tall interfere directly in the cattle´s feeding behavior which require more grazing time when subjected to low sward heights.